Traditional Games on Character Building: Integrating Hide and Seek on Learning - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Muhammad Dewa Zulkhi (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to determine the effect on learning of incorporating the traditional game of Hide and Seek. This type of research employs a mixed-methods. This study used several variables as research categories, including response, peace-loving character, and patriotism, and enrolled a total of 44 students. Descriptive and inferential statistics were used in the data analysis. The integration took place at an Elementary School and a Madrasah Ibtidaiyah in Batang Hari, as evidenced by the response, which reflected the peace-loving nature of patriotism. The result is that each response variable, peace, love, and patriotism, has a significant effect, with a value of sig 0.05, and that each variable is dominant in the good category.